Strategi Peningkatan Portofolio Pembiayaan Melalui Syndicated Financing Di Bank Syariah Kota Medan - Rahmayati Rahmayati (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2020)
This research to determine the strategy of Islamic banks by increasing the financing portfolio through syndicated financing. This research will be conducted at Islamic banks in the city of Medan, namely PT. Bank Sumut Sharia Business Unit by collecting data on financing products from Islamic banks internally and statistical data on syndicated financing products. This research method is designed as a descriptive study, which aims to describe the nature or characteristics of a symptom, event, event that is happening right now. And this research is an explanatory survey which is based on data in the form of financial data from Islamic banks, namely a three-year annual report, 2016, 2017, and 2018 PT. Bank of North Sumatra Sharia Business Unit. The results of the study prove that syndicated financing can increase the North Sumatra Bank's financing portfolio.